Native American architecture - Nabokov, Peter; Easton, Robert, 1940- (New York : Oxford University Press, 1989)
The book presents the building traditions of major tribes in nine regional profiles covering North America, including Alaska and the Canadian Arctic.
Wigwam and longhouse: Northeast and Great Lakes -- Mound, town, and chickee: Southeast -- Earthlodge, grass house, and tipi: Great Plains -- Pit house and extended tipi: Plateau -- Winter house, iglu, and tent: Arctic -- Plank house: Northwest coast -- Wood, earth, and fiber: California -- Hogan, ki, and ramada: Southwest I -- Pueblo: Southwest II.
Includes index.
Bibliography: p. 411-420.
Keywords: Indians of North America -- Dwellings; Indian architecture -- North America